Monismo do corpo: único ponto de partida atualmente possível para o desenvolvimento de uma psicologia científica - Vieira, Gilberto Hauer (1987)
This work begins by reconstituing, from a historical standpoint, the problem of dualism and monism in Psychology. The origin of this reconstitution is settled in Socrates and it's then developped until nowadays, demonstrating that the question still persists. The identification of that origin was determined by the fact that it was when the problem deserved a systematical study and was also characterized as metaphysichal. The question 'to solve concerned then what existed as an autonomous entity, that is, only the 'body', only the 'mind' or both. The solutions proposing only the existence of the mind (monists of the mind) or the existence of mind and body (dualists) would therefore become decisive to the conception of Psychology. Since a decision concerning the aforementioned problem is a condition for the development of a scientific Psychology, Chapter II establishes the conceptions adopted as science, scientific knowledge and scientific method. It's also justified why a great deal of the study should concern the realm of Philosophy of Science, particularly Philosophy of Psychology. In Chapter III, the author demonstrates with greater emphasis that the problem 'mind-body' is still metaphysical, and requires a decision. It's shown that the decision is always taken as a presupposition, if not explicit at least implicit. Once it's been demonstrated that only the body can be considered as representing something that really exists, in a metaphysical sense, the author proceeds to establish the authentic object of Psychology. A 'critical-ealistic' Philosophycal Semantic is then used In order to define this object as the set of properties of the real objet represented by the body and responsible for the manifestations that have always interested Psychology. Finally, in Chapter IV, a systemic model ro represent Nature is conceived. It's rule over by the 'law' of transformation, which results from the interaction of subsystems. Among subsystems, there are those which represent real objects and are referred to as 'Hurnan Body'. They are subjected to the same 'law'. Following the transformation of U23592 into Pb20782, two mathematical functions based on the theory of sets are built. The purpose here is to demonstrate the functioning of the law of transformation, or function of transformation, applicable to all subsystems, which are elements of the system that represent Nature. These and other constructions, when applied to systems that represent the real objects denoted as Human Body, generate a great number of consequences to Psychology. At the end, a specific model to represent the real object denoted as Human Body is presented. It is a subsystem and therefore a system composed of four subsystems: Motor, Emotional, Perceptive and Cognitive. The functioning of the whole and the parts become then ruled over by the law of Transformation.